Pd–Cu interaction in Pd/Cu-MCM-41 catalysts: Effect of silica source and metal content - Benito, Patricia Virginia (2014)
Pd/Cu-MCM-41 catalysts for the hydrodechlorination of CF3OCFClCF2Cl to CF3OCFCF2 were prepared. Palladium- and copper-containing samples (Pd/Cu = 1 molar ratio) were synthesized by adding Pd2+ and Cu2+ during the formation of MCM-41, and then the slurries were aged by microwave-hydrothermal treatment. The effect of the silica source (silicates or TEOS) and total metal loading (2.4 and 4.0 wt.%) on the chemical–physical properties and catalytic performances was studied. Bimetallic silicate-derived samples show features similar to those of the pristine MCM-41, regardless of the total metal content. Conversely, the long-range order of the mesoporous structure decreases for TEOS-derived catalysts, and large metal contents seem to alter the structure for these materials. During template removal by thermal treatment, palladium and copper are on the surface of MCM-41 particles, forming Pd1−xCuxO solid solutions whose composition is silica source-dependent. The amount of copper in Pd1−xCuxO is greater for TEOS-derived samples. After reduction, both Pd- and Cu-enriched alloys were found by XRD in silicate-derived samples, while XPS measurements indicated that the surface of the catalyst is enriched with copper. XRD and XPS analyses on TEOS samples indicated that the surface Cu/Pd ratio is closer to 1, and fcc PdCu alloys with a high copper content were identified. The composition of metallic particles modifies the selectivity, TEOS-derived catalysts being more selective to the target CF3OCFCF2.